Integrating Islamic Values in Online Learning: A Comparative Study of Western and Islamic Education Philosophies - Afif, Nur; Aziz, Abd; Mukhtarom, Asrori; Mubin, Fatkhul; Lubis, Muhammad Riyadi (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThe aim of this research is to examine the application of Islamic values in online learning and compare the principles of online learning from the perspectives of Western Education Theory and Islamic Education Philosophy. This qualitative research employs a literature review methodology. The findings indicate that integrating Islamic values into online learning is essential without compromising these values. The research contrasts practical online learning principles as viewed by Western educational theories and classical Islamic scholarship. A significant difference identified is that Islamic education incorporates worship values, whereas Western educational philosophy focuses solely on the humanitarian process without the worship aspect.AbstrakPenelitian ini bertujuan untuk mengkaji penerapan nilai-nilai Islam dalam pembelajaran daring dan membandingkan prinsip-prinsip pembelajaran daring dari perspektif Teori Pendidikan Barat dan Filosofi Pendidikan Islam. Penelitian kualitatif ini menggunakan metodologi tinjauan literatur. Temuan menunjukkan bahwa mengintegrasikan nilai-nilai Islam dalam pembelajaran daring adalah penting tanpa mengkompromikan nilai-nilai tersebut. Penelitian ini membandingkan prinsip-prinsip praktis pembelajaran daring menurut teori pendidikan Barat dan karya-karya cendekiawan Islam klasik. Perbedaan signifikan yang teridentifikasi adalah bahwa pendidikan Islam mengandung nilai ibadah, sedangkan filosofi pendidikan Barat hanya berfokus pada proses kemanusiaan tanpa aspek ibadah.  How to Cite: Afif, N., Aziz, A., Mukhtarom, A., Mubin, F., & Lubis, M.R. (2024). Integrating Islamic Values in Online Learning: A Comparative Study of Western and Islamic Education Philosophies. TARBIYA: Journal of Education in Muslim Society, 11(1), 27-36. doi:10.15408/tjems.v11i1.40392.